2017
DOI: 10.1093/jhered/esx114
|View full text |Cite
|
Sign up to set email alerts
|

Population Networks Associated with Runs of Homozygosity Reveal New Insights into the Breeding History of the Haflinger Horse

Abstract: Within the scope of current genetic diversity analyses, population structure and homozygosity measures are independently analyzed and interpreted. To enhance analytical power, we combined the visualization of recently described high-resolution population networks with runs of homozygosity (ROH). In this study, we demonstrate that this approach enabled us to reveal important aspects of the breeding history of the Haflinger horse. We collected high-density genotype information of 531 horses originating from 7 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 36 publications
9
47
3
Order By: Relevance
“…The ROHs detected in this study covered 13.17% (295.29 Mb) of the autosomal genome expressed by the SNP loci. The total genome length covered by ROHs is comparable with study of Grilz-Seger et al (2018) and Druml et al (2018) that showed across various breeds the overall genomewide ROH coverage at level 305.1 Mb. But, the study of Grilz-Seger et al (2019a) revealed by use of 700k genotyping array that the genome ROH coverage in Noriker horse depending on the colour variety resulting from different mating strategies.…”
Section: Resultssupporting
confidence: 71%
“…The ROHs detected in this study covered 13.17% (295.29 Mb) of the autosomal genome expressed by the SNP loci. The total genome length covered by ROHs is comparable with study of Grilz-Seger et al (2018) and Druml et al (2018) that showed across various breeds the overall genomewide ROH coverage at level 305.1 Mb. But, the study of Grilz-Seger et al (2019a) revealed by use of 700k genotyping array that the genome ROH coverage in Noriker horse depending on the colour variety resulting from different mating strategies.…”
Section: Resultssupporting
confidence: 71%
“…Obtained proportion of ROHs across the genome of Norik of Muran horse is comparable to other local horse breeds, e.g. Austrian Noriker (Grilz-Seger et al, 2019), Bosnian mountain and Haflinger horses (Druml et al, 2018;Grilz-Seger et al, 2018) or Polish Konik horse (Kamiński et al, 2017). Compared to pedigree analysis, the genomic inbreeding showed the same trend (Fig.…”
Section: Resultssupporting
confidence: 55%
“…Previous studies based upon pedigree and genome‐wide SNP data also illustrated genetic fragmentation of the Noriker population into different coat color strains (Druml et al . , ).…”
Section: Resultsmentioning
confidence: 99%
“…To visualize the population structure of Noriker horses with respect to the different coat color strains, we performed a high‐resolution network analysis based upon an identical‐by‐state‐derived relationship matrix (G), following the description by Druml et al . (). Briefly, we computed genetic distances by subtracting pairwise relationships from 1 and applied the NetView approach in its default setting (number of k nearest neighbors k ‐NN = 10) (Neuditschko et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation